Fisetin protects liver from binge alcohol-induced toxicity by mechanisms including inhibition of matrix metalloproteinases (MMPs) and oxidative stress. (April 2016) - Koneru, Meghana; Sahu, Bidya Dhar; Kumar, Jerald Mahesh; Kuncha, Madhusudana; Kadari, Amrita; Kilari, Eswar Kumar; Sistla, Ramakrishna
Highlights: Fisetin ameliorated acute alcohol-induced liver injury in mice. Fisetin pre-treatment restored the antioxidant and MMP/TIMP balance. Fisetin restored the alcohol-induced alteration of mitochondrial enzymes. Fisetin reduced the alcohol-induced morphological and histological changes. Fisetin as an adjuvant can effectively treat alcohol-induced hepatic damage. Abstract: Alcohol consumption is an addictive disorder causing hepatic steatosis, fibrosis and cirrhosis. The protective effect of fisetin, a bioflavonoid, present in foods like strawberries, apples, persimmons, grapes and onions was studied on murine model of acute alcohol-induced hepatotoxicity. Five doses of 50% ethanol p.o. (10 ml/kg body weight) every 12 hours was used to induce hepatotoxicity in mice. Liver function, oxidative stress, histological changes, mitochondrial function, pro-inflammatory markers, collagen content, and matrix metalloproteinases were assessed. Alcohol treatment produced a significant increase in the oxidative stress markers, disturbed the mitochondrial function, matrix metalloproteinases activities and also induced histological changes in liver tissue. Pre-treatment with fisetin (5 and 10 mg/kg) restored the alcohol-induced alterations in liver function, antioxidant defence, histological changes, mitochondrial respiratory enzymes and matrix metalloproteinases activities. Thus, fisetin has the potential to ameliorate alcohol-induced hepatic damage and may be used as an adjuvant in the treatment of alcohol-induced hepatotoxicity.